The meaning and connotation of the root [Hebrew characters] in the Old Testament - Craig, Glen Stuart (Rhodes University, Faculty of Divinity, Department of Divinity, 1964)
In Chapter One, mention is made of certain features of Old Testament study which should be kept in view in any study such as this. e.g. The Old Testament is a book about God and His relation to man. It is essentially practical in its thought. The conception of Corporate Personality was very fully developed in Israel, and needs to be borne in mind, particularly for an understanding of pre-exilic Israel. Then, too, the Old Testament Is not homogenous in thought, but is virtually a library of books by different authors, written at different times, and in different circumstances. Chapter Two begins with a brlef survey of the relation of the Hebrew root [Hebrew characters] to other Semitic languages with basic connotations. ThIs is followed by a long and detailed analysis of the use of the root [Hebrew characters] in the Old Testament. In this section, the use of the various grammatical forms - the Verb (Qal, Pi'eÌ„l and Riph'iÌ‚l), Adjective and Noun, are examined with reference to men and animals, in their metaphorical use and in certain set phrases. Throughout an attempt is made, according the context, to differentiate between its use with the following connotations: being animated, purely physical existence, activity, revival from ill- health, revival from death, and general prosperIty and welfare. The section is concluded with a brief analysis of some words used as parallels to the root [Hebrew characters]. Bearing in mind that the main purpose of this thesis is to try to discover whether, as used in the Old Testament, the root has any deeper significance, an examination is made in Chapter Three of its use in the context of various relationships. After touching briefly on relationships of animals, a detailed study is made of relationships entered into by man; first in a general sense and then more specifically in the context of Election, Covenant, Cultus and Holy Places, as governed by the Torah and finally, as enjoined by Wisdom teachlng. Although relationships between men and other men, and between men and animals, are discussed, the main emphasis is always on the relationship between man and God. The conclusion drawn is that the root [Hebrew characters] is used to denote an intimate relationship between God and man - a relationship though, in which God is by far the more senior partner. Chapter Four is a brief study of the development of a belief in an After-Life in the Old Testament, emphasizing only those aspects which are relevant to the purpose of this Thesis. A brief description of early beliefs in an After-Life is followed by a discussion of tho Prophetic influence and the resistance to any such belief until after the Exile. Post-exilic developments, which took the Hebrews almost to the point of belief in a life after death, are discussed under the headings: "The Problem of Reward and Retribution" and "The Religious need for God". Finally a brief examination is made of the two late passages in the Old Testament where definite reference is made to a life after death. The Root, [Hebrew characters], it is concluded, is used to describe the deepest of all experiences of men - everlasting fellowship with God.
Keywords: Hebrew language -- Roots; Bible -- Criticism, Textual